HYGIENE DAN SANITASI INDUSTRI PABRIK PENGOLAHAN TAHU CV TAHU ATB DI KECAMATAN KURANJI KOTA PADANG - Fitria, Friska Eka; Onasis, Aidil; Sugriarta, Evino (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Hygiene sanitation in the food industry is a system of environmental care which includes creating a clean environment, hygienic work methods, maintaining the health of workers and fostering clean attitudes, habits and behaviors. This study aims to determine the hygiene and sanitation of the tofu factory industry Cv. ATB Tofu in Kuranji Subdistrict, Padang City which consists of the requirements and application of hygiene and sanitation of tofu processing factories. This research is a quantitative descriptive research. The research was conducted at the tofu factory Cv. Tofu ATB Kuranji District Padang City from July to October 2023. The samples used in this study were 30 tofu processing plant workers. The research measuring instrument used questionnaire with data analysis using univariate analysis. The results obtained 76.7% of hygiene and sanitation requirements in the good category and 83.3% with the application of hygiene and sanitation of the tofu processing process in the good category. It is expected for entrepreneurs of the tofu factory Cv. Tofu ATB to improve hygiene and sanitation by paying attention to the production environment, equipment and facilities, and personal hygiene of workers. Keywords: Hygiene, Sanitation, Tofu Processing Factory